726 Consenting for Surgery During the Pandemic: A Closed-Loop Audit on Discussing and Documenting the Risks of Hospital-Acquired COVID-19. (12th October 2021) - Kim, W A; Wu, F; Al-Afifi, S; Sebastian, J
Abstract: Introduction: There is limited data on the nosocomial transmission of COVID-19. The Royal College of Surgeons (RCS) have published guidance on consenting for surgery, which includes discussing the risks of hospital-acquired COVID-19 with patients as part of the consenting process 1 . We performed a closed-loop audit on our unit's consenting practice to assess compliance using the RCS guidelines as the audit standard. Method: A retrospective case review, including elective and emergency procedures, were identified from June to November 2020. Consent forms were reviewed for evidence of patient counselling for the risks of hospital-acquired COVID-19 using the RCS guidance for comparison. Positive SARS-CoV-2 RT-PCR swabs and radiological imaging suggestive of COVID-19 within 30-days were also assessed. We undertook the 1st cycle of data collection in September. Following this, we used a local meeting to educate the surgical team. The 2nd cycle (re-audit) was performed in December. Results: In cycle 1, from June to August 17/29 (59%) case notes documented the discussion of the COVID-19 risk. None of these patients contracted the virus. In cycle 2, from September to November, compliance improved to 28/33 (80%). One (3%) patient had contracted COVID-19. They had a positive SARS-CoV-2 RT-PCR swab and signs suggestive of COVID-19 on their CT chest. Conclusions: The re-audit demonstrated an improvement in our consenting practice from 59% to 80%. One patient had hospital-acquired COVID-19 during our period of data collection, which reflects current data that suggests nosocomial COVID-19 is rare 2 . With new advisory guidelines, it is important to discuss these risks.